Faktor Risiko Kelelahan pada Pengendara Ojek Daring di Jabodetabek dan Denpasar - Manuel, Josua Aditya; Wirawan, I Made Ady (Media Kesehatan Masyarakat Indonesia, 2020)
Fatigue in motorists is a serious problem that causes traffic accidents and deaths every year, including online motorcycle taxi riders. Motorcycle riders contribute 72.7% to all injuries caused by traffic accidents in Indonesia. This study aims to determine the risk factors of fatigue in online motorcycle taxi riders based on demographic characteristics, job characteristics, and work stress. A cross-sectional study was conducted involving 306 online motorcycle taxi riders in Jabodetabek and Denpasar between January and June 2018, which was selected by convenience sampling. Data were collected through interviews using questionnaires and analyzed using multiple logistic regression with the forward LR method. The results showed that 68.1% of online motorcycle taxi riders experienced fatigue. The risk factors associated with fatigue in online motorcycle taxi drivers were work stress (AOR=3.66;95%CI=2.01-6.66), lack of physical activity (AOR=2.11;95% CI=1.27-3.51), duration of sleep <7 hours (AOR=1.73;95%CI=1.04-2.87), marital status (AOR=2.07;95%CI=1.18-3.64), and age <30 years (AOR=2.52; 95%CI=1.43-4.45). Meanwhile, the work area, nutritional status, rest duration, and other jobs were not proven to be related to work fatigue. Fatigue in online motorbike riders is associated with work stress, physical activity, sleep duration, marital status, and age, so preventive measures can be applied by considering these factors.